HPLC Separation of 2-Ethyl-5(6)-methylpyrazine and Its Electroantennogram and Alarm Activities on Fire Ants (Solenopsis invicta Buren) - Ya-Ya Li (Molecules, 2018)
2-Ethyl-3,6-dimethylpyrazine (EDMP) was an alarm pheromone component isolated from the mandibular gland of the red imported fire ant, Solenopsis invicta Buren. Several pyrazine analogues have been previously found to elicit significant alarm responses in S. invicta workers. This study aimed to separate the commercially available 2-ethyl-5(6)-methylpyrazine (EMP), i.e., a mixture of 2-ethyl-6-methylpyrazine (2E6MP) and 2-ethyl-5-methylpyrazine (2E5MP), and to examine both electroantennogram (EAG) and behavioral responses of S. invicta workers to EMP and the purified isomers. HPLC separations were achieved using a polysaccharide chiral stationary phase (Chiralpak AD-H) column with both mobile phases: Cyclohexane/isopropanol, and hexane/isopropanol. A ratio of 99:1 was selected for the separation of EMP at semipreparative level. The structures of the isomers obtained through the cyclohexane/isopropanol mobile phase were confirmed by detailed analyses of 2D-HSQC- and -HMBC-NMR data. The two isomers showed differential methine C–H correlations evidenced by 2D-HMBC-NMR spectra. The two concentrated fractions obtained through hexane/isopropanol mobile phase were subjected to EAG test and behavioral bioassay on S. invicta workers. The two HPLC−purified isomers, 2E6MP and 2E5MP, and their mixture (1:1) at same dose elicited similar EAG and alarm responses, indicating that these two isomers are equally active. The 2D-NMR−spectroscopic characterization, and electrophysiological and alarm activities of 2E6MP and 2E5MP were reported here for the first time.